2021
DOI: 10.1038/s41467-021-25268-1
|View full text |Cite
|
Sign up to set email alerts
|

Redox-enabled direct stereoconvergent heteroarylation of simple alcohols

Abstract: The direct transformation of racemic feedstock materials to valuable enantiopure compounds is of significant importance for sustainable chemical synthesis. Toward this goal, the radical mechanism has proven uniquely effective in stereoconvergent carbon-carbon bond forming reactions. Here we report a mechanistically distinct redox-enabled strategy for an efficient enantioconvergent coupling of pyrroles with simple racemic secondary alcohols. In such processes, chirality is removed from the substrate via dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Chiral iridium complex 16 could catalyze the borrowing hydrogen cascade reaction of 2-methylpyrrole 18 with (±)-1phenylethanol 19, affording product 20 in moderate yield with some extent of enantio-control. 73 It should be noted that the enantioselectivity of phosphoric acid did not benefit the enantio-control. Chiral palladium dimer complex 17 was able to catalyze the 1,2-addition reaction of 4-methoxyphenylboronic acid 22 with imine 21, affording 23 in quantitative yield with moderate enantioselectivity (Scheme 5c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral iridium complex 16 could catalyze the borrowing hydrogen cascade reaction of 2-methylpyrrole 18 with (±)-1phenylethanol 19, affording product 20 in moderate yield with some extent of enantio-control. 73 It should be noted that the enantioselectivity of phosphoric acid did not benefit the enantio-control. Chiral palladium dimer complex 17 was able to catalyze the 1,2-addition reaction of 4-methoxyphenylboronic acid 22 with imine 21, affording 23 in quantitative yield with moderate enantioselectivity (Scheme 5c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These two complexes were then examined in the asymmetric reactions (Scheme b). Chiral iridium complex 16 could catalyze the borrowing hydrogen cascade reaction of 2-methylpyrrole 18 with (±)-1-phenylethanol 19 , affording product 20 in moderate yield with some extent of enantio-control . It should be noted that the enantioselectivity of phosphoric acid did not benefit the enantio-control.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated the synthetic utility of this method in the synthesis of a histamine H1 receptor agonist. Finally, Zhao and colleagues demonstrated the redox-enabled direct enantioconvergent heteroarylation of simple alcohols in the presence of an achiral iridium catalyst and chiral phosphoric acid (Scheme d) . Both racemic benzylic and aliphatic secondary alcohols could be effectively coupled with pyrroles to generate products with high ee’s; the authors propose that the enantiodetermining step involves the reduction of a stabilized carbocation bearing a chiral phosphate counterion.…”
Section: Deoxygenative Functionalizationmentioning
confidence: 99%
“…Since the 21 st century, there has been extensive research into the application of hydrogen-borrowing reactions for the efficient and selective construction of the C–N bond and C–C bond. This research has made a substantial contribution to the advancement of organic synthesis, yielding a range of highly economical asymmetric synthesis methods and facilitating the creation of novel chiral heterocyclic compounds. However, this strategy has predominantly relied on the use of expensive transition metals, and has been plagued by challenges related to poor stereoselectivity. Highly selective hydrogen borrowing examples were reported until recently …”
Section: Introductionmentioning
confidence: 99%